2017
DOI: 10.4103/1119-3077.180046
|View full text |Cite
|
Sign up to set email alerts
|

Can serums be replaced by Mueller-Hinton agar in germ tube test?

Abstract: It is suggested that inexpensive MHA is a fast, appropriate, and reliable medium for the probable diagnosis of GTT and C. albicans; however, additional studies are still needed to define other Candida species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…The possible cause of variability in germ tube positivity rate may be attributed to the incubation temperature andtime. 4,8,13,14 Trypticase soy broth had a sensitivity rate of 72.65% in our study; which is similar to the findings of Arora et al and Makwana et al 6,10 In contrast, Kim et al and Deorukhar et al had reported a higher sensitivity rates of 100% and 94%respectively in trypticase soya broth. 7 In this study, 61.71% of C. albicans isolates showed germ tube test positive in peptone water.…”
Section: Discussionsupporting
confidence: 90%
“…The possible cause of variability in germ tube positivity rate may be attributed to the incubation temperature andtime. 4,8,13,14 Trypticase soy broth had a sensitivity rate of 72.65% in our study; which is similar to the findings of Arora et al and Makwana et al 6,10 In contrast, Kim et al and Deorukhar et al had reported a higher sensitivity rates of 100% and 94%respectively in trypticase soya broth. 7 In this study, 61.71% of C. albicans isolates showed germ tube test positive in peptone water.…”
Section: Discussionsupporting
confidence: 90%
“…Further, YEPD medium had sensitivity (81.25%) and also Kim et al, (2002) reported 100% positivity at 39º, comparing germ tube induction in rabbit serum at 37ºC.The possible cause of variability in germ tube positivity rate may be attributed to the incubation temperature and time. (Sachin C. Deorukhkar et al, 2012;Kim et al, 2002;Atalay et al, 2017) Trypticase soya broth had a sensitivity rate of 72.65% in our study; which is similar to the findings of (Arora et al, 2003) and (Gopee E. Makwana et al, 2012). In contrast, Joshi KR et al, and (Sachin C. Deorukhkar et al, 2012) had reported a higher sensitivity rates of 100% and 94%respectively in Trypticase soya broth.…”
Section: Resultssupporting
confidence: 82%
“…Germ tube induction in agar media was conducted by dripping 10 μL of 0.5 McFarland fungi suspension into 1 x 1 cm 2 agar. 18 Cover slip was placed to facilitate easier examination. The agar was then incubated for three hours at 37°C.…”
Section: Gem Tube Inductionmentioning
confidence: 99%
“…Interestingly, Atalay et al (2017) found that MHA was the best media for germ tube induction compared to human serum. 18 Distinct factor affects the yeast-to-hyphal transition in agar media. Villa et al (2020) stated that C. albicans hyphal growth in agar is influenced by the embedded surroundings or conditions.…”
Section: Germ Tube Induction In Agarmentioning
confidence: 99%